Book Review: Epprecht, M. 2013: Sexuality and Social Justice in Africa: Rethinking Homophobia and Forging Resistance. (April 2015) - Jones, Ben
Epprecht, M. 2013: Sexuality and Social Justice in Africa: Rethinking Homophobia and Forging Resistance. London: Zed Books. 232 pp. £12.99 paperback. ISBN: 9 78178 0323817.